Strategi Pengembangan Usaha Menggunakan Metode Quantitative Strategic Planning Matrix pada UMKM Mokey - Sandra, Winnie; Suherman, Suherman; Kusumanto, Ismu; Nofirza, Nofirza; Harpito, Harpito (Universitas Batanghari Jambi, 2025)
The aim of this research is to identify an analysis of the internal and external conditions of Mokey MSMEs and to design the best alternative strategy proposal in order to increase sales and maintain the business being run using the SWOT (Strength, Weakness, Threat, Opportunity) matrix and the QSPM (Quantitative Strategic Planning Matrix) method. The research results showed that the position of MSME Mokey was categorized as high in utilizing internal and external conditions with a total of IFE 3.9 and EFE 3.8 and the results of analysis using the QSPM method showed that there were 7 strategies that MSME Mokey could use to increase sales and maintain the business.